發新話題
打印

93台南女中

推到噗浪
推到臉書

回復 3# chihming 的帖子

第四題
非 lagrange multiplier 的解法
設 \( (x,y)=(4+r\cos\theta,3+r\sin\theta), r \geq 0\)
代入 \(4x^{2}-24xy+11y^{2}+40x+30y-145=4(x-4)^{2}-24(x-4)(y-3)+11(y-3)^{2}-20=0\)
整理可得 \(\displaystyle 7\cos2\theta+24\sin2\theta=15-\frac{40}{r^2}\)
因此 \(r^2 \geq 1\)  (疊合)
得 \( r\geq 1\)

lagrange multiplier 的解法
設 \(f(x,y)=4x^{2}-24xy+11y^{2}+40x+30y-145\)
,\(g(x,y)=(x-4)^{2}+(y-3)^{2}\)
則 \(\nabla f(x,y)=[8x-24y+40,-24x+22y+30]\)
,\(\nabla g(x,y)=[2(x-4),2(y-3)]\)
若 \(g(x,y)\) 在條件 \(f(x,y)=0\) 上有極值,則 \(\nabla g(x,y)=\lambda \nabla f(x,y)\)
即 \(\displaystyle \frac{8x-24y+40}{2(x-4)}=\frac{-24x+22y+30}{2(y-3)}\)
\(\displaystyle \Rightarrow \frac{4x-12y+20}{x-4}=\frac{-12x+11y+15}{y-3}\)
\(\displaystyle \Rightarrow \frac{4(x-4)-12(y-3)}{x-4}=\frac{-12(x-4)+11(y-3)}{y-3}\)
\(\displaystyle \Rightarrow 4-12\frac{y-3}{x-4}=11-12\frac{x-4}{y-3}\)
設 \(\displaystyle \frac{x-4}{y-3}=t\),得 \(12t^{2}-7t-12=0\) 即 \(\displaystyle t=\frac{4}{3} \vee -\frac{3}{4}\)
若 \(\displaystyle \frac{x-4}{y-3}=t=\frac{4}{3}\),設 \((x,y)=(4+4s,3+3s)\) 代回 \(f(x,y)=0\) 得 \(\displaystyle s^{2}=-\frac{4}{65}\) 矛盾
若 \(\displaystyle \frac{x-4}{y-3}=t=-\frac{3}{4}\),設 \((x,y)=(4-3s,3+4s)\) 代回 \(f(x,y)=0\) 得 \(\displaystyle s^{2}=\frac{1}{25}\)
因此 \(g(x,y)\) 有極值 \(25s^{2}=1\)

[ 本帖最後由 czk0622 於 2021-4-18 22:54 編輯 ]

TOP

發新話題